2020
DOI: 10.1017/s1751731120000154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alternative feed additives to medicinal zinc oxide on productivity, diarrhoea incidence and gut development in weaned piglets

Abstract: The use of medicinal zinc oxide (ZnO) must be phased out by 2022, thus prompting an urgent need for alternative strategies to prevent diarrhoea in weaner piglets. The objectives of this study were to assess the impact on weaner piglet performance, diarrhoea incidence and gut development, when (1) dietary ZnO supplementation was substituted by alternative commercial products based on macroalgae, specific probiotics or synbiotics, or (2) dietary ZnO inclusion was reduced from 2500 to 1500 ppm. A total of 4680 DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 24 publications
3
29
0
Order By: Relevance
“…This review outlines two applications for reduction of antibiotic use, including for growth promotion and disease prevention. An overview of possible antibiotic alternatives for growth promotion derived from previous studies is presented in Supplementary Table 1 (Cha et al, 2012;Kim et al, 2014;Yoon et al, 2014;Zeng et al, 2014;Devi et al, 2015;Gois et al, 2016;Hossain et al, 2016;Lee et al, 2016;Peng et al, 2016;Sbardella et al, 2016;Tang et al, 2016;Upadhaya et al, 2016;Wan et al, 2016;Lan et al, 2017;Lei et al, 2017;Ma et al, 2017;Pan et al, 2017;Wu et al, 2017;Huang et al, 2018;Lei et al, 2018;Samolińska et al, 2018;Sayan et al, 2018;Seo et al, 2018;Xu et al, 2018;Pei et al, 2019;San Andres et al, 2019;Wang et al, 2019;Duarte et al, 2020;Petry et al, 2020;Ren et al, 2020;Satessa et al, 2020;van der Peet-Schwering et al, 2020;Wei et al, 2020;Zhang et al, 2020;Sun et al, 2021;Wang et al, 2021). These vary considerably from chemical compounds, biologically active substances, and microbially derived products.…”
Section: Alternatives To Antibioticsmentioning
confidence: 99%
“…This review outlines two applications for reduction of antibiotic use, including for growth promotion and disease prevention. An overview of possible antibiotic alternatives for growth promotion derived from previous studies is presented in Supplementary Table 1 (Cha et al, 2012;Kim et al, 2014;Yoon et al, 2014;Zeng et al, 2014;Devi et al, 2015;Gois et al, 2016;Hossain et al, 2016;Lee et al, 2016;Peng et al, 2016;Sbardella et al, 2016;Tang et al, 2016;Upadhaya et al, 2016;Wan et al, 2016;Lan et al, 2017;Lei et al, 2017;Ma et al, 2017;Pan et al, 2017;Wu et al, 2017;Huang et al, 2018;Lei et al, 2018;Samolińska et al, 2018;Sayan et al, 2018;Seo et al, 2018;Xu et al, 2018;Pei et al, 2019;San Andres et al, 2019;Wang et al, 2019;Duarte et al, 2020;Petry et al, 2020;Ren et al, 2020;Satessa et al, 2020;van der Peet-Schwering et al, 2020;Wei et al, 2020;Zhang et al, 2020;Sun et al, 2021;Wang et al, 2021). These vary considerably from chemical compounds, biologically active substances, and microbially derived products.…”
Section: Alternatives To Antibioticsmentioning
confidence: 99%
“…Probiotics and prebiotics appear to be promising candidates for ZnO and in-feed antibiotic alternatives; however, the mechanisms involved in probiotic- and prebiotic-induced protection in the pig gut remain to be understood. Supplementation of lactic acid bacteria and fermented rapeseed meal induced similar or significant improvement of pig growth performance compared with zinc supplementation by improving mucosal development, inhibiting intestinal inflammation, and modulating the gut microbiota ( Satessa et al., 2020 ). Similar to ZnO supplementation, probiotic and prebiotic supplementation increased the abundance of Prevotella ( Satessa et al., 2020 ), which has been characterized as a resident gut commensal and a major contributor to polysaccharide breakdown in pigs ( Pajarillo et al., 2014a , Pajarillo et al., 2014b ).…”
Section: Zincmentioning
confidence: 99%
“…In addition, all treatments including ZnO reduced Lactobacillus spp. in the pig gut ( Satessa et al., 2020 ), suggesting that other beneficial bacteria may promote gut immunity in pigs. Other studies have reported that ZnO increased Lactobacillus spp.…”
Section: Zincmentioning
confidence: 99%
See 2 more Smart Citations